Photo-narrative frames: Using visuals with narrative research in applied linguistics. (November 2021) - Greenier, Vincent; Moodie, Ian
Abstract: A narrative frame is a data collection instrument comprising a series of sentence prompts that facilitate the elicitation of participant narratives by scaffolding the writing process. Narrative frames allow multiple respondents to compose narratives that are comparable in length, form, and substance, thus allowing the researcher to focus on more precise research aims than are generally possible with more open-ended types of narrative data. In this article, we discuss the rationale for narrative frames and their use in recent research, revisiting their strengths and limitations as research instruments. Following this, we use data from a project investigating the professional identities of expatriate native-speaking English teachers to illustrate the use of photo-narrative frames, an innovation that supplements written stories with photographs from participants' professional experiences. As narratives provide a means of understanding the experiences of others, visual data, such as photographs, can amplify the context, further connecting participant narratives to insights about the complexity of their lives and behaviors. The study details the procedures, from designing and piloting the frames to data collection and analysis. We show how visual-textual layering and integration occurs in a participant's stories and how the images help the participant convey their professional narratives to others. We conclude by considering the ethical issues with collecting and disseminating photographs from participants before making suggestions for future research, focusing on further innovations that can blend visual methods with narrative research, for example, by taking advantage of social media platforms and on-line survey software.